2019
DOI: 10.1002/aoc.5354
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxides as support for the synthesis of nickel sulfide–indium oxide nanocomposites for photocatalytic, antibacterial and antioxidant performances

Abstract: NiS (nickel sulfide)–In2O3 (indium oxide) nanostructures and NiS–In2O3 decorated on graphene oxide (GO) were demonstrated by ultrasonic/hydrothermal method. The structural study demonstrates the preparation of bixbyite and hexagonal phase of In2O3 and NiS for all of the synthesized catalysts. The band gap of the synthesized catalyst was determined to be in the range of 2.30–3.00 eV. A morphological evaluation by field emission scanning electron microscopy of NiS–In2O3 decorated on graphene oxide shows support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…NiS-IO-GO Ultrasonic/hydrothermal [28] WO 3 -IO Sol-gel [29] SnO 2 -IO Precipitation [30] Y 2 O 3 -IO Co-precipitation/sol-gel [27] Mn(II) doped IO foam Sol-gel [31] Organic-inorganic IO foam Sol-gel [32] Colloidal IO nanoparticles Laser ablation [33]…”
Section: Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…NiS-IO-GO Ultrasonic/hydrothermal [28] WO 3 -IO Sol-gel [29] SnO 2 -IO Precipitation [30] Y 2 O 3 -IO Co-precipitation/sol-gel [27] Mn(II) doped IO foam Sol-gel [31] Organic-inorganic IO foam Sol-gel [32] Colloidal IO nanoparticles Laser ablation [33]…”
Section: Systemmentioning
confidence: 99%
“…In this respect, the preparation methods that govern the generation of specific structural features, porosity and defects in the bulk nanomaterials. It is reported that ITO and nickel doped ITO nanomaterials exhibit X-ray diffraction peaks similar to that of pure In 2 O 3 with cubic bixbyite structure [27][28][29][30]. To calculate the band gap energy (BGE), the optical reflectance spectrum of a bulk nanomaterial can be recorded and then converted into its absorption spectrum.…”
Section: Indium Oxide Based Bulk Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antibacterial potential of Ag 2 S, CdS, CuS MoS 2, and ZnS has been studied many times. There are few publications on the antimicrobial action of more exotic binary sulfides like SnS 2, CoS 2, NiS, and In 2 S 3. Binary sulfides are most often complemented by another compounds like oxides to get the composite with good antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…[3] In general, metal sulfides and oxides are being used as photocatalysts. [4,5] The photoactivity of ZnO and TiO 2 on the degradation of MB (methylene blue) as an organic dye under UV irradiation was studied by Štrbac and co-workers. [6] The photocatalytic efficiency of ZnO and TiO 2 has some weaknesses, such as rapid charge recombination, activation under UV light, and lack of active sites.…”
Section: Introductionmentioning
confidence: 99%